2020
DOI: 10.18632/aging.202199
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of circulating tumor DNA in pancreatic cancer: a systematic review and meta-analysis

Abstract: Increasing evidence has revealed the potential correlation between circulating tumor DNA (ctDNA) and the prognosis of pancreatic cancer, but inconsistent findings have been reported. Therefore, a meta-analysis was performed to evaluate the prognostic value of ctDNA in pancreatic cancer. The Embase, MEDLINE, and Web of Science databases were searched for relevant articles published until April 2020. Articles reporting the correlation between ctDNA and the prognosis of pancreatic cancer were identified through d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…We demonstrated an independent prognostic value of baseline ctDNA detection in our study, an observation that confirms previously published results, including several meta-analyses [13,14]. Our HRs of 2.1 and 2.0 for PFS and OS, respectively, were slightly lower than in our previously published pilot study and the pooled data analyses [11].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We demonstrated an independent prognostic value of baseline ctDNA detection in our study, an observation that confirms previously published results, including several meta-analyses [13,14]. Our HRs of 2.1 and 2.0 for PFS and OS, respectively, were slightly lower than in our previously published pilot study and the pooled data analyses [11].…”
Section: Discussionsupporting
confidence: 92%
“…ctDNA is DNA that is released from apoptotic and necrotic tumour cells into the bloodstream [ 10 ]. Several studies, including multiple meta‐analyses, support the prognostic potential of ctDNA detection in plasma, demonstrating that patients in whom ctDNA is detected have a significantly worse prognosis than those in whom it is not detected [ 11 , 12 , 13 , 14 , 15 , 16 ]. Some studies have also explored the relationship between ctDNA and imaging, showing associations between the dynamics of ctDNA and the radiological response [ 11 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…ctDNA is a valued diagnostic PDAC tool. Moreover, ctDNA is believed to play an important role in PDAC prognosis [80]. KRAS ctDNA MAF has been associated with PDAC clinical stage [81].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Ueberroth al. [ 21 ] and Yin et al [ 22 ] found that circulating tumor cells (CTCs) and circulating tumor DNA (ctDNA) could be detected in the blood of N 0 pancreatic cancer patients who achieved pathological complete remission after radical resection of pancreatic cancer or neoadjuvant therapy, which suggests a poor prognosis and a high risk of distant metastasis [ 23 ]. Similarly, our study found that among the 4491 PDAC with N 0 and distant metastasis patients, 1538 (34.24%) also had distant metastasis, which means that the risk of recurrence and metastasis in N 0 patients may have been previously underestimated.…”
Section: Discussionmentioning
confidence: 99%